The Hunger Games in Mexico. The havoc of crime within the framework of structural violence - Acevedo Alemán, Jesús; De León Alvarado, Cesár Arnulfo; Barrera, Irán (Trabajo Social UNAM, 2017)
Like the novel The Hunger Games by Suzanne Collins, which tells an epic adventure of a post-apocalyptic country in which its characters must fight to the death, while they are watched on national television, in Mexico this macabre game has moved out of the realm of science fiction and books and materialized in every corner of our country. Upon reflecting on the subject of the havoc of crime this analogy comes to mind. Nowadays Mexicans, when leaving home, must compete, not so much for finding conditions of well being, but of survival. The presence of a violent culture, added to the increase and diversification of criminal activity produces a scene straight from the imagination of Leigh Whannell, author of the series Saw or better known as The Game of Fear, in which “Jigsaw”, the architect of evil, more than killing his victims, traps them in situations he calls “games” or “tests” in order to test his victims’ will to live, faced by all kinds of physical and psychological torture. To venture into the havoc of crime, it is necessary to understand the conditions which exist in our context, especially to try to identify the adverse social architecture, or, the scenarios in which we have been trapped and which challenge us to prove our will to live. In this sense, the present essay points to the reflection of so called structural violence. In reality this is not a “macabre game” or “Hunger Games” but a crucial component for understanding the violent dynamics of our country. The referential frameworks which provide the structural conditions make it possible to produce a macro vision of the various variables which come together in the violent dynamics of subjects, and the way in which these detonate accelerated increases in episodes of extreme hostility, presented by criminal, violent activity of organized crime, which directly affects the most vulnerable, such as children and young people.